2022
DOI: 10.1093/pa/gsac022
|View full text |Cite
|
Sign up to set email alerts
|

‘We Can’t Afford to be a Branch Office’: The Territorial Dynamics of the British Labour Party, 2015–2019

Abstract: Despite having delivered devolution, the British Labour Party has faced significant challenges in adapting to, and competing effectively in, a multi-level political space. This article explores this dynamic in the context of a pivotal period of change (2015–2019), in which the party was led by Jeremy Corbyn, a political outsider, and when British politics was riven by Brexit. In this article we highlight the operation of a key strategic duality underlying the territorial politics pursued by both Scottish and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…UK politics still largely operates under a majoritarian system with a strong notion of parliamentary sovereignty which centralises considerable power in the PM who handpicks the executive. The devolution of powers to Scottish, Welsh, and Northern Irish legislatures presented a clear challenge to this model, prompting claims of 'bi-constitutionalism' and the emergence of alternative visions of sovereignty (Flinders 2010;Richards & Smith 2015;Brown Swan & Kenny 2024). However, the repoliticisation of devolution post-2016 has indicated that processes which cement the power of a narrow Westminster elite persist, epitomised by the UK government's deployment of a Section 35 Order to block Scottish legislation in 2023 (Baldini et al 2022).…”
Section: The Westminster Modelmentioning
confidence: 99%
“…UK politics still largely operates under a majoritarian system with a strong notion of parliamentary sovereignty which centralises considerable power in the PM who handpicks the executive. The devolution of powers to Scottish, Welsh, and Northern Irish legislatures presented a clear challenge to this model, prompting claims of 'bi-constitutionalism' and the emergence of alternative visions of sovereignty (Flinders 2010;Richards & Smith 2015;Brown Swan & Kenny 2024). However, the repoliticisation of devolution post-2016 has indicated that processes which cement the power of a narrow Westminster elite persist, epitomised by the UK government's deployment of a Section 35 Order to block Scottish legislation in 2023 (Baldini et al 2022).…”
Section: The Westminster Modelmentioning
confidence: 99%